2019
DOI: 10.1037/cou0000329
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of gender among Arab American women: A qualitative study.

Abstract: Even within counseling psychology's multicultural literature, attention to persons of Arab descent remains limited. Despite counseling psychologists' goal of becoming more multiculturally proficient, the dearth of systematic empirical research on the counseling of Arab Americans is glaring. This exploratory consensual qualitative research (CQR) investigation analyzed interview data from 11Arab American women to explore their experiences at the intersections of ethnic identity and gender. In addition to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…In addition to the rejection of their American identities by society, several participants were perceived as “too American” in their communities. A similar finding emerged in Abdel-Salam et al’s (2019) study of Arab American women in which participants described feeling rejected by other Arabs and Muslims and difficulty upholding familial values. The literature suggests that for Arab Americans specifically, conflicts between child and parent values may complicate Arab Americans’ attempts to develop bicultural identity (Chen & Sheldon, 2012).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition to the rejection of their American identities by society, several participants were perceived as “too American” in their communities. A similar finding emerged in Abdel-Salam et al’s (2019) study of Arab American women in which participants described feeling rejected by other Arabs and Muslims and difficulty upholding familial values. The literature suggests that for Arab Americans specifically, conflicts between child and parent values may complicate Arab Americans’ attempts to develop bicultural identity (Chen & Sheldon, 2012).…”
Section: Discussionsupporting
confidence: 73%
“…Another area of interest that requires more investigation is differences in the experiences of discrimination based on one’s ability to pass as White, as Arab Americans vary in their skin color and hair texture (Naber, 2000). In a sample of Arab American women, Abdel-Salam et al (2019) found that participants felt that they were perceived as racially ambiguous by others. Some researchers note that the microaggressions Muslims experience may vary as a function of their ability to pass, which is important to examine to learn more about the unique types of microaggressions experienced by this diverse religious group (Nadal et al, 2012).…”
Section: Invisible Minoritymentioning
confidence: 99%
“…The young people in this study experienced adolescence and the transition to emerging adulthood in the United States and as such were raised with the American normative nature of substance use for young people (Davis et al, 2019). But they also reside at the intersection of multiple cultures, thus culturally informed education programs (within schools, mosques, or community organizations) focused on risks associated with tobacco, alcohol, and marijuana use need to include young Arab Americans (e.g., Hammad et al, 2014) and Muslims (Ahmed et al, 2014) The religious, cultural, and gender-related stigma associated with substance use and misuse might make it difficult for a young person struggling with substance abuse to seek help (Abdel-Salam et al, 2019). Previous studies reflect that some young Arab Americans report that drinking alcohol is normative for their age group, and yet tend to believe that these habits should end when people get married and have children (Arfken et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the influence of these disinhibitory factors is likely quite strong for young Muslim Arab Americans in general and for young Muslim women in particular as many of the religious and cultural expectations related to substance use are strongly gendered. The traditional gender roles and the focus on maintaining reputation that are a part of both the Arab American culture and Islam might make it particularly stigmatizing for a young Muslim woman to engage in alcohol or drug use (Abdel-Salam et al, 2019;Mahmood, 2012). However, the intersectional influences of culture, religion, and gender are less clear for tobacco use.…”
Section: Religiosity Gender and Intersectional Influences Among Arab American Youthmentioning
confidence: 99%
See 1 more Smart Citation